Milczenia Aleksandra Wata - Mitzner, Piotr (Colloquia Litteraria, 2012)
The author focuses on the periods of Aleksander Wat’s poetic silence. He states that although after 1926 Wat – perhaps “out of disgust for language” and perhaps he felt that literature in a traditional sense is unnecessary – he becomes silent as a poet, he does not lose a great linguistic sensibility (a “bird” language of one of fellow-prisoners in 1931). An important event in the context of Wat’s thinking of the lanaguge, word, was his acquaintance with Evgeni Dunajewski in 1941 in a cell in Łubianka in Moscow who became Wat’s linguistic “mentor”. When returning to poetry (1940) Wat encounters difficulties: the poet obstinately searches for a language suitable for the description of the world plunged into communism, he was convinced that everything was already said and simultaneously that a lot of truths were not touched upon, the poet wavered between love and hate for words. And besides words there was silence, holy silence which for Wat had a metaphysical dimension, and it was the silence (and not speech) that he enumerated as one of the instruments of cognition (Trzy starości. Trzecia [Three ages. The third one]).